The Effect Of Economic And Social Factors On Tourism Demand For Malaysia And Selected Neighbouring Countries - Borhan, Nurbaizura (2018)
Tourism industry has become one of the important sectors in the ASEAN region. However, the growth in the number of tourist arrivals has reduced in recent years. Due to the economic importance of the tourism industry, this study investigates the long-run relationship and short-run dynamic between tourism demand with that of selected economic variables and social indices. Utilizing data from 23 countries, the variables employed in this study consist of four economic variables as well as five social indices and five one-off events. To achieve the objectives, the study has employed a few econometric techniques that include Engle-Granger (EG) 2-step procedure, autoregressive distributed lag (ARDL) modelling approach, static and heterogeneous panel data techniques and also Kalman filter (KF) estimation technique. The result of cointegration analysis revealed that there exist long-run relationship among the selected variables. The results from panel data techniques yield higher percentage of correct sign for the model coefficients with exchange rate and income level generally have positive impact on tourism demand. The relative price and substitute relative price are found to have a mixture of positive and negative impact. This study also revealed that the SARS outbreak, FLU pandemic and euro debt crisis have negative impact on the tourism demand for Malaysia while the H1N1 pandemic and global financial crisis do not have a negative impact on the number of tourist arrivals.